Is marriage a viable strategy of reducing HIV/AIDS infection among women in Zimbabwe? - Gumbo, Jeremy Dickson (My University, 2011)
Background: Using Zimbabwe Demographic Health Survey 2005-06 data, this study examined the viability of marriage as a prescription in reducing HIV/AIDS infection among Zimbabwean women. In a population where heterosexual intercourse is the main mode of transmission and the practice of multiple concurrent partners is highly prevalent and tolerated, the study examined HIV/AIDS prevalence among women according to their marital status and coresidence status. The study argues that low HIV/AIDS prevalence among currently married women, and coresiding women relative to never married and formerly married women, and non coresiding women respectively suggest that marriage is a viable behavioral measure in reducing HIV/AIDS infections. Methods: A total of 4,491 women undertook HIV testing and were used in this study to examine HIV/AIDS prevalence according to marital status. Descriptive statistics from cross tabulations manipulated by STATA 11 were used in exploring HIV/AIDS prevalence among these women. Furthermore, various multivariate logistic regressions were carried out to isolate the effects of marital status, socioeconomic, demographic and sex risk behavior factors on HIV/AIDS infection. Results: The major finding of the study was that currently married women had lowest HIV/AIDS prevalence compared to both never married and formerly married women. Furthermore, HIV/AIDS prevalence was lower among women coresiding than those not coresiding. Conclusion: There is a strong association between marital status and HIV/AIDS status among Zimbabwean women, and marriage is a likely viable measure in reducing HIV/AIDS infections.